Investigating the effect of perlite particles on ilmenite-based oil well cement - Abdulmalek Ahmed; Ahmed Mohamed; Salaheldin Elkatatny (Journal of Petroleum Exploration and Production Technology)
Abstract Well cementing is a critical operation for maintaining the stability of an oil well. Various additives have been employed to modify cement properties to meet downhole requirements in the formulation of oil-well cement. In this study, experimental work was conducted to investigate the impact of perlite on the properties of ilmenite-based cement. Several techniques were used to characterize the materials, such as X-ray fluorescence (XRF), particle-size distribution analysis, and scanning electron microscopy (SEM). Samples with varying perlite concentrations were prepared to examine the rheological behavior, particle settling, mechanical properties, and permeability. Additionally, computerized tomography (CT) scanning was employed to assess the homogeneity of the prepared cement samples. The results indicated that the ideal concentration of perlite to improve cement characteristics was 4% by weight of cement (BWOC). Adding perlite significantly improved the rheological behavior of the cement slurry, as shown by a 30% reduction in plastic viscosity, a 330% increase in yield point, and a 214% increase in gel strength. Perlite also effectively reduced the settling of particles, particularly ilmenite particles, to a very low percentage of 0.1%, as confirmed by the homogeneity observed in the CT scan images. Incorporating perlite into the cement composition enhanced the cement’s strength, resulting in an 88% increase in compressive strength and a 195% increase in tensile strength. Adding perlite particles had a minor effect on Poisson’s ratio, with an increase of only 0.75%. Furthermore, the inclusion of perlite assisted in reducing the cement permeability by 66%.